2016
DOI: 10.1016/j.ttbdis.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasma phagocytophilum in small rodents in France

Abstract: Anaplasma phagocytophilum is an emerging zoonotic tick-borne pathogen affecting a wide range of mammals. Rodents are suspected to be natural reservoirs for this bacterium, but their role in the epidemiologic cycles affecting domestic animals and wild ungulates has not been demonstrated. This study aimed to improve our knowledge on A. phagocytophilum prevalence in Apodemus sylvaticus, A. flavicollis and Myodes glareolus using data collected in 2010 in one area in eastern France and in 2012-2013 in two others ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…The difference of A . phagocytophilum prevalence between wood mice and bank voles had already been partly analysed and discussed elsewhere (Chastagner et al ., ). The I .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The difference of A . phagocytophilum prevalence between wood mice and bank voles had already been partly analysed and discussed elsewhere (Chastagner et al ., ). The I .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, Chastagner et al . () proposed exposure to I . trianguliceps ticks as a possible explanation of the highest prevalence found in bank voles compared to wood mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Europe, prevalence of A. phagocytophilum (22.8%) was reported among rodents belonging to the species Apodemus sylvaticus, Apodemus flavicollis and Myodes glareolus, which were sampled in different regions of France (CHASTAGNER et al, 2016). In Germany, Obiegala et al (2014) found low prevalence of A. phagocytophilum (1.1%) among the rodent species A. sylvaticus, Myodes glareolus and A. flavicollis.…”
Section: Molecular Detection Of Anaplasmataceae Agents Inmentioning
confidence: 95%
“…This could in part be due to their immunity to infection or other attributes such as size of rodent. For example, it is thought that older animals may have a higher immunity to infection in comparison to juveniles [33,34]. Alternatively, larger rodents might be more susceptible to infection based on the mere fact that they can sustain a larger population of ticks and hence are more likely to become infected.…”
Section: Discussionmentioning
confidence: 99%